THE PRAGMATIC FEATURES OF JURIDICAL TEXTS IN UZBEK AND ENGLISH LANGUAGES - Khushbokova Gulimoh (Journal of new century innovations, 2023)
Abstract: Without underestimating the position of language in any other sphere of social life, it is right to emphasize that its importance is extremely important in the legal sphere. Because the development of the new society being built on the basis of democratic principles in Uzbekistan is determined by the rule of law. When the issue is put in this way, the perfect knowledge of the legal language is not only the task of lawyers, but it becomes a life requirement for all members of society to be properly aware of it. Why is that? Because a citizen who is aware of the contents of legal documents recognizes his rights, understands well which part of his activity is in line with the interests of the society and the people, the current laws and regulations. Therefore, he builds his life on this basis.